Subretinal AAV2.COMP-Ang1 suppresses choroidal neovascularization and vascular endothelial growth factor in a murine model of age-related macular degeneration. (April 2016) - Lambert, Nathan G.; Zhang, Xiaohui; Rai, Ruju R.; Uehara, Hironori; Choi, Susie; Carroll, Lara S.; Das, Subrata K.; Cahoon, Judd M.; Kirk, Brian H.; Bentley, Blaine M.; Ambati, Balamurali K.
Abstract: To assess whether Tie2-mediated vascular stabilization ameliorates neovascular age-related macular degeneration (AMD), we investigated the impact of adeno-associated virus-mediated gene therapy with cartilage oligomeric matrix protein angiopoietin-1 (AAV2.COMP-Ang1) on choroidal neovascularization (CNV), vascular endothelial growth factor (VEGF), and hypoxia-inducible factor (HIF) in a mouse model of the disease. We treated mice with subretinal injections of AAV2.COMP-Ang1 or control (AAV2.AcGFP, AAV2.LacZ, and phosphate-buffered saline). Subretinal AAV2 localization and plasmid protein expression was verified in the retinal pigment epithelium (RPE)/choroid of mice treated with all AAV2 constructs. Laser-assisted simulation of neovascular AMD was performed and followed by quantification of HIF, VEGF, and CNV in each experimental group. We found that AAV2.COMP-Ang1 was associated with a significant reduction in VEGF levels (29–33%, p < 0.01) and CNV volume (60–70%, p < 0.01), without a concomitant decrease in HIF1-α, compared to all controls. We concluded that a) AAV2 is a viable vector for delivering COMP-Ang1 to subretinal tissues, b) subretinal COMP-Ang1 holds promise as a prospective treatment for neovascular AMD, and c) although VEGF suppression in the RPE/choroid may be one mechanism by which AAV2.COMP-Ang1 reduces CNV, this therapeutic effect may be hypoxia-independent. Taken together, these findings suggest that AAV2.COMP-Ang1 has potential to serve as an alternative or complementary option to anti-VEGF agents for the long-term amelioration of neovascular AMD. Highlights: AAV2.COMP-Ang1 may be an efficacious therapy for neovascular AMD. Subretinal AAV2.COMP-Ang1 induces COMP-Ang1 protein expression in the RPE/choroid. Subretinal AAV2.COMP-Ang1 suppresses laser-induced VEGF protein expression in the RPE/choroid. Subretinal AAV2.COMP-Ang1 reduces laser-induced CNV volume.